P62/SQSTM1 is required for the protection against endoplasmic reticulum stress-induced apoptotic cell death. (1st December 2016) - Park, Jeong Su; Oh, Sue Young; Lee, Da Hyun; Lee, Yu Seol; Sung, Su Haeng; Ji, Hye Won; Lee, Moon Joo; Lee, Yong-ho; Rhee, Sue Goo; Bae, Soo Han
Abstract: Endoplasmic reticulum (ER) stress is triggered by various cellular stresses that disturb protein folding or calcium homeostasis in the ER. To cope with these stresses, ER stress activates the unfolded protein response (UPR) pathway, but unresolved ER stress induces reactive oxygen species (ROS) accumulation leading to apoptotic cell death. However, the mechanisms that underlie protection from ER stress-induced cell death are not clearly defined. The nuclear factor erythroid 2-related factor 2 (Nrf2)-Kelch-like ECH-associated protein 1 (Keap1) pathway plays a crucial role in the protection of cells against ROS-mediated oxidative damage. Keap1 acts as a negative regulator of Nrf2 activation. In this study, we investigated the role of the Nrf2-Keap1 pathway in protection from ER stress-induced cell death using tunicamycin (TM) as an ER stress inducer. We found that Nrf2 is an essential protein for the prevention from TM-induced apoptotic cell death and its activation is driven by autophagic Keap1 degradation. Furthermore, ablation of p62, an adapter protein in the autophagy process, attenuates the Keap1 degradation and Nrf2 activation that was induced by TM treatment, and thereby increases susceptibility to apoptotic cell death. Conversely, reinforcement of p62 alleviated TM-induced cell death in p62-deficient cells. Taken together, these results demonstrate that p62 plays an important role in protecting cells from TM-induced cell death through Nrf2 activation.